THE IMPACT OF POLITICAL AND ECONOMIC SITUATION ON THE PSYCHOLOGICAL WELL-BEING OF PAKISTANI PEOPLE (Journal of Medical & Health Sciences Review, 2025)
Background: Pakistan is going through a financial crisis and recent wave of political intolerance has polarized the society to an unprecedented level, adding to the already high prevalence of mental health issues and traditional, deeply ingrained religious intolerance in Pakistan.Methodology: Cross-sectional analytical study design was used for this study, which was completed from march to June 2023 with sample size of 225 using a purposive sampling technique. A validated and reliable Political and economic analysis checklist and DASS-21 checklist was used for data collection. Descriptive and inferential statistic was calculated through SPSS 20.Results: In the current study the total participant was 225, where the number of male was in majority (80.4%) compare to female participant (19.6%). In political analysis the majority of participants (39%) responded  that accountability, political stability, rule of law, control on corruption, government effectiveness , and freedom of press level is “extremely low”. While in economic analysis, most of the participants (56%) report that their monthly expenses, inflation, fear of investment and unemployment is  “high”. Furthermore, the high mean score was report of stress (0.96 ± 0.48), followed by depression (0.90 ± 0.57), and anxiety (0.88 ± 0.48).Conclusion: The study concluded that Pakistan face range of difficulties as political turmoil and economic crisis which break all their own records. Moreover political and economic instability, and profession is mild negative correlated with DASS, while Age, gender, marital status, education and profession are moderately positive correlated each other.